Kebudayaan Jawa : ragam kehidupan kraton & masyarakat di Jawa 1922-1998 - Rama, Ageng Pangestu (Godean, Yogyakarta : Cahaya Ningrat, 2007)
History of Javanese kings, nobles, courts, and civilization, based on manuscripts, 1222-1998
Daftar pustaka: p. 461-466
Keywords: Java (Indonesia) -- Kings and rulers; Java (Indonesia) -- Social life and customs; Java (Indonesia) -- Civilization